Data Science and Big Data Analytics Proceedings of IDBA 2024 - Mishra, Durgesh; Yang, Xin-She; Unal, Aynur; Jat, Dharm Singh (Learning and Analytics in Intelligent Systems, 2025)
XIV, 819 p. 332 illus., 282 illus. in color.